Evaluation of botanicals against mustard aphid, Lipaphis erysimi (Kaltenbach) in Mid Hills of Meghalaya: EVALUATION OF BOTANICALS AGAINST MUSTARD APHID IN MID HILLS OF MEGHALAYA - PARTHA DEBNATH; RACHNA PANDE; SANDIP PATRA; JAYANTA LAYEK; G I RAMKRUSHNA; REMIIO NEWYEAR BAMON; DIPALI MAJUMDAR (Journal of Oilseeds Research, 2018)
A field experiment was carried out at ICAR Research Complex for NEH Region, Umiam to evaluate some botanicals against mustard aphid Lipaphis erysimi. The experiment was laid out in randomized block design with eight treatments and three replications. The mustard seeds(cv. Varuna) was sown during third week of October. The treatments viz., Bakain (Melia azedarach) leaf extract (5%aqueous solution), Lantana (Lantana camara) leaf extract (5% aqueous solution), Turmeric (Curcuma longa) rhizome powder (5% aqueous solution), Marigold (Tagetes erecta) leaf extract (5% aqueous solution), Vasaka (Adhatoda vasica) leaf extract (5% aqueous solution), chloropyrifos 20% EC (200 g a.i./ha) and imidacloprid 17.8% SL (25 g a.i./ha) along with control were applied at fifteen days interval. Results revealed that Melia azedarach was best among all botanicals with 50.5-61.9 per cent and 50.7-57.5 per cent reduction of aphid population during first and second spray, respectively. Next best treatment was Adhatoda vasica followed by Curcuma longa, Lantana camara and Tagetes erecta. Among all the treatments, chloropyrifos and imidacloprid recorded maximum reduction of aphid population after both the spray. Although all botanicals showed less toxicity towards non-target organisms whereas chlorpyriphos and imidacloprid were highly toxic to honey bees and coccinellid beetles.